EFFECTS OF AGE AT PEPPER SEEDLING TRANSPLANT AND MAIZE POPULATION ON THE GROWTH AND PRODUCTIVITY OF MAIZE-PEPPER INTERCROP ON AN ALFISOL IN IBADAN (2014)
Mixed cropping of pepper (Capsicum frutescens L.) with arable crops is a popular cropping system among peasant farmers of southwestern Nigeria. The yield of pepper is affected by age at transplanting as well as population of the intercrop. However, there is paucity of information on the combined effects of population of intercropped maize and the age of pepper seedling transplant on the growth and productivity of the system. Therefore, the effects of age of pepper at transplanting and population of intercropped maize on the growth and yields of the two crops were investigated at the Institute of Agricultural Research and Training, Ibadan, for two years. Two varieties of Cayenne pepper, NHVI-A and Sombo were intercropped with maize variety, DMR-EM-Y, which was sown at three population of 26667, 35556 and 53333 plants/ha. The treatments were assigned in a randomized complete block design with three replicates. In another experiment, the two varieties of pepper were intercropped with two weeks old maize at 26667 plants /ha at 3, 4, 5, 6 and 7 weeks after sowing (WAS). Data collected included plant height stem diameter, number of leaves and number of branches and percent seedling survival; maize grain yield and pepper fresh fruit yield were subjected to ANOVA at P = 0.05. Land Equivalent Ratio(s) were also calculated. Population significantly reduced the height of sole maize (93.1cm) more than intercropped maize at 53333 plants/ha (136.5cm); and stem diameter of sole maize (2.36cm) than intercropped maize at 26667 plants/ha (2.6cm), respectively at 8 WAP. Compared with sole crop, intercropped maize at 53333 plants/ha was significantly taller (136.5cm) with Sombo, while at 26,667 plant/ha, it had bigger stem diameter (2.51 and 2.61 cm) when intercropped with the two varieties. The grain yields of intercropped maize (2.68 and 2.24 tha-1) at population of 35,556 and 26,667 plants/ha, respectively were however significantly lower than 4.3 and 4.2 tha-1 obtained for intercropped maize at 53,333 plants/ha with NHVIA and Sombo, respectively. Generally, Sombo produced higher yield than NHVIA, while of number fruits and yield of the two varieties of pepper were significantly reduced by intercropping with maize at the three population. The yield (1944kgha-1) of sole NHVIA was however significantly higher than the corresponding value of 1320kgha-1 for Sombo. Pepper seedling transplanted into maize at 6 and 7 WAS for NHVIA and 5 and 7 WAS for Sombo had significantly taller plants, bigger stem diameter and higher number of leaves and branches at 8 WAT than the corresponding younger transplants. Similarly, 6 and 7-week old transplants of the two pepper varieties produced significantly higher yields than the corresponding younger transplants. Maximum yield (1,860kgha-1) was produced by 7-week old Sombo transplant intercropped with maize. Maize intercropped with 6 and 7-week old Sombo transplants resulted in the higher LER of 1.99 and 2.06 respectively compared with the corresponding values of 1.66 and 1.75 for NHVIA. The results obtained confirmed the productivity of maize-pepper intercrop of 6-week and 7-week old transplants are introduced into 2-week old maize at 26,667 plants/ha.